Money and the transmission of monetary policy - Seth Carpenter; Selva Demiralp (TÜSİAD-Koç University Economic Research Forum, 2009)
The transmission mechanism of monetary policy has received extensive treatment in the macroeconomic literature. Most models currently used for macroeconomic analysis exclude money or else model money demand as entirely endogenous. Nevertheless, academic research and many textbooks continue to use the money multiplier concept in discussions of money. We explore the institutional structure of the transmission mechanism beginning with open market operations through to money and loans to document that the mechanism does not work through the standard multiplier model or the bank lending channel. Our analysis, however, does not reflect on the existence of a broader credit channel.
Keywords: E51; E52; 330; monetary transmission mechanism; money multiplier; lending channel; Transmissionsmechanismus; Geldpolitik; Geldschöpfung; Kreditkanal; VAR-Modell; Schätzung; USA